Venture Capital and Market Reaction to the Disclosure of Information - Mosayeb Beyannejad (Journal of Global Pharma Technology, 2017)
The transaction volume behavior is closely related to the inhomogeneity of information among investors. Investors in financial markets are generally divided into two groups of informed and uninformed investors. To gain an abnormal return, informed investors make deals based on the confidential information of a security or the information they have and other market actors are lack of them. Uninformed investors, on the other hand, buy and sell stocks based on other reasons, including having liquidity. This carries with it the matter of unsecure choices according which uninformed investors are placed in an unpleasant condition. The leading question, thus, is that how the investors’ decisions, in the face of abnormal return and unexpected earnings, affect the unusual stock trading volume in the Tehran Stock Exchange. Given the research limitations, all companies listed in the Tehran Stock Exchange were sampled by the systematic elimination method (screening). The general purpose of this research is to study the effect of decisions made by venture capitalists on trading on the Tehran Stock Exchange. This is a practical research study, in terms of purpose, with an ex post facto design. Here, three hypotheses, including the effect of CGO investors on abnormal trading volume when companies’ financial information is disclosed, the correlation between unexpected earnings and trading volume and the abnormal return when companies’ financial information is disclosed, were assessed. Based on results, there is a positive and significant correlation between investors’ CGO and the abnormal trading volume when companies’ financial information is disclosed. Investors’ CGO has a strong impact on the relation between unexpected earnings and fluctuations in the stock prices and trading volume. There is a negative and significant correlation between investors’ CGO and the abnormal return when companies’ financial information is disclosed. Besides all factors affecting decision-making, investors check all overhangreturns. However, the stock returns have a trivial impact on this research. Keywords: Investors’ CGO, Unexpected Earnings, Abnormal Return, Trading Volume.